Up-regulation of CatSper genes family by selenium - Movahedin Mansoureh; Mohammadi Shabnam; Mowla Seyed (BMC, 2009)
Abstract Background CatSper1-4 are a unique family of sperm cation channels, which are exclusively expressed in the testis and play an important role in sperm motility and male fertility. Despite their vital role in male fertility, almost nothing is known about the factors regulating their expression. Here, we investigated the effects of selenium (Se) on the expression of CatSper genes and sperm parameters in aging versus young male mice. Methods Forty 11-13 months aging male mice and forty 2-3 months young adult male mice were used. The animals were divided in two experimental groups: first group including aging males and second group comprising of young adult males, both treated with Se. The experimental groups were injected intra-peritoneally with Se (0.2 mg/kg) daily, for up to 5 weeks. Two other groups, aging and young adult mice without Se treatment were used as controls. All the animals were rapidly sacrificed by cervical dislocation on the days 21, 28, 35 and 42 after Se treatment. Subsequently, the morphology of the collected sperms was analyzed, and one of the testes from each mouse used for semi-quantitative RT-PCR. The significancy of the data was analyzed using ANOVA. Results and Discussion Our data revealed that there was a significant up-regulation of CatSper genes in the experimental groups compared to the control ones. Furthermore, the results of sperm analysis showed that the sperm parameters were improved in the aging as well as young adult male mice following Se treatment. Conclusion Se treatment in the aging subjects could up-regulate the expression of CatSper genes, and therefore results in elevation of sperm motility. Furthermore, Se treatment improved sperm parameters, especially morphology and viability rates.